The importance of using biomechanical indicators in the pedagogical interventions of physical education and sports teachers in secondary education - bouabdallah, sbaa; Mouissi, Farid; torki, ahmed (sports creativity, 2025)
Physical education and sports aim to achieve the general goals of education by building and developing several aspects of the learner's personality. This depends on its content, teaching contexts, and the teacher's ability to apply the knowledge acquired during their training. Teachers receive diverse lessons and in-depth knowledge in the humanities, biology, and the practical aspects of education. Physical education and sports differ from other subjects due to their kinetic nature and their connection to the body, which possesses mechanical properties in its normal movements. This research aims to identify the biomechanical indicators that teachers employ during their pedagogical interventions. To achieve this goal, we adopted a descriptive approach and selected a random sample of secondary school teachers. A questionnaire was specifically designed to collect data on the research variables. After statistical analysis, it was found that there is a low level of this knowledge among the research sample, a limited application of this knowledge in the teaching process, and a general lack of its application in the educational field.